Ko-infeksi Virus Hepatitis B dan Virus Hepatitis C pada Penderita HIV/AIDS di Surakarta, Indonesia - Raden Artheswara Sidhajati; Afiono Agung Prasetyo; Yulia Sari (Nexus Biomedika, 2013)
Background: One problem in HIV treatment is HBV/HCV co-infection due to their similarity in the transmission routes. HBV/HCV co-infection is believed increasing the risk of hepatotoxicity, hepatocellular carcinoma, steatosis, fibrosis, and also rapidly lead to AIDS in the HIV patients. The purpose of this study was to find out the status of HBV/HCV co-infection among HIV patients in Surakarta. Methods: In November-December 2011 all of HIV patients (n=65) visited the Voluntary Counseling and Testing in Moewardi General Hospital Surakarta were involved in the study. Clinical data and blood samples were retrieved from all patients. Serological assays to detect the presentation of HBsAg and anti-HCV were performed in all samples. Results: There were 17% (11/65) HIV patients infected with the hepatitis viruses. Six point two percent (4/65) was HBsAg+, 10.8% (7/65) was anti-HCV+, and 0% with triple infection. There were 57.1% (4/7) females and 42.8% (3/7) males detected with anti-HCV+. Males and females, each was found 50% (2/4) in HBsAg+. Ninety one percent (10/11)HIV patients with both HBV or HCV co-infection were under 50 years old .None of routine blood test was significant with HBsAg+ or anti-HCV+. Conclusions: Several HIV patients had co-infection with Hepatitis B Virus and Hepatitis C Virus, and most of them were females under 30 years. HIV patients should be checked the status of HBV and HCV co-infection in order to have a better therapeutic management. Keywords: HIV co-infection, Hepatitis B Virus, Hepatitis C Virus